An investigation of the role of a selected out of school time reading programme on learners' reading behaviours and attitudes - Williams, Sarah Marcella (Rhodes University, Faculty of Education, Department of Education, 2017)
Due to the lingering damage from the Apartheid era and Bantu education, South Africa is still battling to rectify the inequalities in schools in previously disadvantaged areas. The lack of a reading culture and very poor literacy assessment scores in these areas is cause to include even out-of-school time to help remedy these problems. This study seeks to add to the body of literature by investigating the influence of two selected out-of-school time reading programmes on learners' reading attitudes and behaviours within the South African context. Drawing from the New Literacy Studies (Gee, 1991; Street, 1995) and the Theory of Planned Behaviour (Ajzen, 1991), this Mixed- Method approach study examined the role that two out of school reading programmes played in the development of reading behaviours and attitudes of learners from township area called Simonstown, in the Eastern Cape Province. Located within the Pragmativist Paradigm, Mixed Method Research Approach, and Explanatory Design Method as a research design, the study used pre- and post-intervention quantitative questionnaires, semi-structured interpreter-facilitated interviews, structured observations, and the out of school reading programme as an intervention to generate data. The research site and study participants were purposively selected. They included 10 learners from 2 out of school reading programmes that benefited from funding and literacy project training and support called Nal'ibali. The study was designed to evaluate the effectiveness of these out of school reading programmes in improving learners reading behaviours and attitudes, and how the OST reading programmes influenced the reading behaviours and attitudes of the parents. Findings from the data concluded that the certain factors in the OST reading programme in conjunction with the positive influence of the parents and siblings own reading attitudes had a positive effect on learners' reading attitudes and behaviours.
Keywords: Uncatalogued